WATER VENDORS PARTICIPATION IN DOMESTIC WATER SUPPLY IN UNGUWA UKU, TARAUNI LOCAL GOVERNMENT, KANO STATE, NIGERIA - Bello, Nura Isyaku; Shehu, Aminu; Abubakar, Ahmad S.; Bello, Abdulkadir; Iman, Mahmoud Z. (FUDMA JOURNAL OF SCIENCES, 2021)
Water vending is seen as a signing of a failure in piped-borne water supply systems, it still plays significant role in providing water especially to urban dwellers in many parts of developing countries, Nigeria inclusive. Therefore, this study examined water vendors participation in domestic water supply in Unguwa Uku, Tarauni LGA Kano state. The data used in this research collected from both primary and secondary sources. The data collected was analyzed using descriptive statistics, where simple percentages and tables used. The data analysis revealed that 57.4% of the residents in the study area patronized the services of water vendors. Patronage of vendor service dominated the frequency with 64.9% of respondent’s patronage of vended water. Seasonal variation in vended water supply patterns exist in the study area, with dry season account for the highest water demand and most supplies occurred during morning and evening hours. Based on the challenges bedevilled water-vending activities, the study recommends that vendors should be recognized as an integral part of the system as this may help in the design and implementation of more comprehensive policies that better serve poor end-users, by ensuring greater accessibility and affordability of water vendor’s service.